Induced resistance in rice against insects - Karban, R.; Chen, Y. (Cambridge University Press, 2007)
Vaccinations are the mainstay of western preventive medicine, and they have been used to protect some crops against disease and insect pests. We consider rice as a model for protection using induced resistance since it is one of the most important staple crops and there have been significant new developments in: cross-resistance among rice insects, chemical pathways involved in induced resistance, sequencing the rice genome and expression of genes conferring resistance against rice insect pests. Insect attack has been found to cause lesions that kill planthopper eggs and early stages of gall midges. Damaged plants released volatiles that made them less likely to be chosen by planthoppers and more attractive to parasitoids. Chemical elicitors have been developed for dicotyledonous plants and these can induce resistance in rice, although rice does not fit models developed to explain signalling in dicots. For example, salicylic acid did not increase in rice after infection by pathogens and did not appear to be the mobile signal for induced resistance against pathogens although it was involved in induced responses to phloem-feeding insects. Jasmonic acid acted as a signal in some induced responses to pathogens as well as chewing insects. Many of the genes associated with induced resistance in rice have recently been mapped, and techniques are being developed to incorporate them into the genome of cultivated varieties. Attempts to control insect pests of rice will affect interactions with pathogens, predators and parasites, and other organisms in this agroecosystem.